Profil Darah Pada Kucing Selama Proses Kesembuhan Luka Melalui Teknik Skin Flaps Rotasi Yang Dirawat Dengan Dry Dressing Dan Moist Dressing: Blood Profile of Cats during the Wound Healing Process using the Rotation Flap with both Dry and Moist Dressing - Erwin Erwin; Rusli Rusli; Fidella Diva Jones (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2020)
The skin flap is one of the techniques employed to reconstruct defects and close wounds. This study aims to observe the blood profile in cats during the healing process of rotation skin flaps that were treated with a dry and moist dressing. This study used six male cats within the age of 1-2 years old and weighed among 2-4 kg, divided into two treatment groups. All of the specimens were treated with the following procedure; the fur on the abdominal area was shaved and disinfectant was applied to the area between the os sacrum and os femur, lastly, 2 cm2 triangle wound was deliberately made on the area. The treatment of the wound was done by the rotation skin flaps method. Group 1 was treated with sterile bandage and group 2 was treated with sofratulle®. Blood samples were taken from the cephalica antebrachii vein on the 1st, 3rd, 6th, and 12th days. The erythrocytes, hemoglobin, hematocrit, platelets, leukocytes, neutrophils, basophils, eosinophils, monocytes, and lymphocytes were counted by hematology analyzer. The results showed that there is a significant difference (P<0.05) in the increase of neutrophil levels between the group treated with sterile kassa (P-1) and the group treated with sofratulle® (P-2). The number of the cats’ red blood cells rose on the 3rd day and rose again on the 12th day after the treatment with a significant difference (P<0.05) during the observation. In conclusion, the rotation flaps treatment method with dry dressing and moist dressing in the wound healing process affected the cats’ blood profile and the moist dressing was preferred to the dry dressing.